Kinetics of the Binding Process of Furan Moulding Sands, Under Conditions of Forced Air Flow, Monitored by the Ultrasonic Technique - Natalia Matonis (Archives of Foundry Engineering, 2023)
The paper presents the results of research on the kinetics of the binding process of self-hardening moulding sands with an organic binder under conditions of forced air flow at various pressure values. Three moulding sands made using urea-furfuryl resin Furanol FR75A technology were studied. The moulding sands were prepared on a base of quartz sand with an average grain size of dL = 0.25, 0.29 and and 0.37 mm , with permeability values of 306 , 391 and and 476 m 2/10 8Pa ∙ s (for ρ0 = 1.60 , 1.60 and and 1.61 g/cm 3, respectively). The research was conducted for a resin content of 1% with a constant proportion of hardener to resin, which was equal to 50%. Samples of the tested moulding sands were blown with air at pressures of 0.1, 0.2, 0.4, 0.6, 0.8, and 1.0 bar. The kinetics of the hardening process was monitored using ultrasound technology, according to a previously developed methodology [1]. The research was carried out on an ultrasound testing station equipped with a temperature chamber and an airflow reducer. The tests were conducted at a temperature of 20°C, and of the air flow pressure on the changes in ultrasonic wave velocity in the hardening mouldins sand as a function of time, the kinetics of the hardening process, and the degree of moulding sand hardening were determined. Additionally, the influence of the moulding sand permeability on the course of the hardening process at a constant air flow pressure was determined.